Sebuah Analisis Perkembangan Desain Muzzle Brake Pada SL Rifle 41 - Muhammad Alief Ramadhana; Heri Budi Wibowo; Robertus Heru Triharjanto; Lutfi Adin Affandi; Donny Haryogi Ramadhan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The research explores advancements in muzzle brake designs for lightweight rifle firearms, aiming to control recoil during firing. The SL Rifle 41 from World War II serves as a historical example, highlighting challenges such as gas escaping near the muzzle, rapid cooling, and piston fouling. The gas expansion difference between the barrel and piston poses operational issues. The firearm shooting process involves high-temperature, high-pressure propellant gas released through the muzzle brake, creating a complex 3D instability problem. The shockwave from the muzzle blast significantly impacts the muzzle brake surface. Modern SL Rifle designers seek to enhance projectile muzzle velocity and After-Action Gas Powder (AAPG) simultaneously, addressing recoil energy through opposing impulses. The research employs a literature review method, analyzing concepts, theories, and findings. The SL Rifle's operational mechanism uses a direct gas impingement system, offering simplicity but accumulating carbon particles. Muzzle brake models feature a primary body and baffles strategically designed for gas dispersion and recoil reduction. Detailed examination of brake muzzle/barrel material objects and established muzzle brake models illustrates engineering considerations, enhancing understanding of design and characteristics. The comprehensive design aims to optimize performance, durability, and shooting stability while minimizing wear associated with carbon buildup. In conclusion, the evolution of muzzle brake design contributes to enhanced firearm performance, ensuring smoother firing, reduced recoil, increased accuracy, and control. Ongoing advancements cater to diverse user needs in military, law enforcement, and civilian contexts, reflecting a commitment to improving firearm technology.